PRODUCT QUALITY IMPROVEMENT CHANNEL C AT PT. SINARINDO MEGAH PERKASA WITH SIX S - Herman, Hashemi Berthshanda; Soecahyadi, Soecahyadi; Zuhria, Siti Aminatu (Sustainable Environmental and Optimizing Industry Journal, 2023)
In the current era of global competition, many companies were looking for alternative solutions to compete with other companies in order to survive in competition, one of which is by improving product quality. Product quality can be seen from the number of defective products produced by the   product.   This   study   aimed   to analyze Channel C defective products at PT. Sinarindo Megah Perkasa in order to improve its quality. The data used is Channel C production from 2015-2022 with a total production of 3,860 products with 73 defective products. The results showed that the causes of defective products in Channel C came from several factors which were analyzed using a fishbone diagram including machine, human, environmental, method, and material factors. The DPMO value obtained was 56,735.75 with a sigma level of 3.0828. The recommended improvements were to carry out regular maintenance on the machine, make notes on the size of the machine roll, add people for Quality Control , make Standard Operating Procedures (SOP), and provide detailed training to operators after the SOP is implemented.